Pengaruh Mekanisme Corporate Governance Terhadap Konservatisme Akuntansi Dengan Intensitas Fair Value Sebagai Pemoderasi - Kazbarani Alvino; Nurzi Sebrina (Wahana Riset Akuntansi, 2020)
The purpose of this research is to examine the effect of corporate governance mechanisms that are moderated by fair value on the level of accounting conservatism. The corporate governance mechanism consists of an independent commissioner, an institutional ownership structure, a foreign ownership structure and audit quality.  Research conducted on manufacturing companies and financial companies listed on the Stock Exchange period 2016-2018, purposive sampling method was used to determine the research sample so that 93 manufacturing companies and 52 financial companies was obtained. Hypothesis testing is done by multiple regression methods. The results showed that the independence of commissioners had a positive effect on the level of accounting conservatism. In manufacturing companies, institutional ownership structure does not affect the level of conservatism, whereas in financial companies, institutional ownership structure influences the level of accounting conservatism. Other corporate governance mechanisms, foreign ownership and audit quality, do not influence the level of accounting conservatism in both manufacturing and financial companies. The intensity of fair value in both sectors of the company has a negative effect, or weakens the relationship of corporate governance mechanisms to the level of accounting conservatism Keywords: Accounting Conservatism; Fair Value; Corporate Governance